2010
DOI: 10.1590/s0100-40422010000800006
|View full text |Cite
|
Sign up to set email alerts
|

Estudo químico e atividade antibacteriana do caule de Aristolochia esperanzae kuntze (Aristolochiaceae)

Abstract: Recebido em 8/10/09; aceito em 13/5/10; publicado na web em 17/9/10 CHEMICAL STUDY AND ANTIBACTERIAL ACTIVITY OF STEM OF Aristolochia esperanzae Kuntze (ARISTOLOCHIACEAE). From the ethanolic extract of the stem of A. esperanzae ethyl and methyl fatty acid esters, fatty acids, aristolochic I and II acids, and β-cubebin were isolated. In addiction asarinin, populifolic and 2-oxo-populifolic acids, aristolactams AIa and AII, and sitosterol 3-O-β-D-glucopyranoside were also isolated and firstly described in the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 8 publications
(12 reference statements)
1
3
0
1
Order By: Relevance
“…Electrospray ionization mass spectrometry (ESIMS) showed pseudomolecular ion signal at m/z 364.03 [M + Na] + and high resolution fast atom bombardment mass spectrometry (HR-FABMS) afforded M+1 ion signal at m/z 342.0620 which was corresponding to the molecular formula C 17 H 12 NO 7 (calculated for 342.06138). 1 H NMR and 3 C-NMR spectra were matched with those of AA-1 which were previously reported [28]. The correlation among each NMR signal was confirmed by 2D HSQC and HMBC.…”
Section: Resultssupporting
confidence: 78%
“…Electrospray ionization mass spectrometry (ESIMS) showed pseudomolecular ion signal at m/z 364.03 [M + Na] + and high resolution fast atom bombardment mass spectrometry (HR-FABMS) afforded M+1 ion signal at m/z 342.0620 which was corresponding to the molecular formula C 17 H 12 NO 7 (calculated for 342.06138). 1 H NMR and 3 C-NMR spectra were matched with those of AA-1 which were previously reported [28]. The correlation among each NMR signal was confirmed by 2D HSQC and HMBC.…”
Section: Resultssupporting
confidence: 78%
“…The aristolochic acids, which are commonly found in plants of the genus Aristolochia [ 14 ], were not detected in the present study. Studies have shown that aristolochic acids have nephrotoxic, carcinogenic and mutagenic effects [ 15 , 16 , 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, several Aristolochia species have shown antimicrobial activity against panels of microrganisms. 5,6 The essential oil from the roots of A. orbicularis, composed by about 40 volatile compounds, showed high repellency against the corn borer Sitophilus zeamais. 7 The present study on the antimicrobial activity of Aristolochia orbicularis was performed as a part of an established program to investigate the antimicrobial potential of local medicinal plants.…”
mentioning
confidence: 99%